Automated Scrolling Using Speech Recognition (International Journal of Engineering and Computer Science, 2018)
The Automated Scrolling Using speech recognition is a promising technique which allows users to scroll through a document with minimum effort and in a smart manner. Speech recognition is being used to perform speech to text conversion of the user’s input which is then processed to accomplish automated scrolling. Google speech recognition API and python speech recognition library are used for efficient extraction of user speech input. A string matching algorithm is used to keep track of user speech input which is converted to text and the document which is to be scrolled. The paper discusses all the modules present in the creation of a proficient automated scrolling system using speech recognition.